2017
DOI: 10.1186/s12866-017-1055-x
|View full text |Cite
|
Sign up to set email alerts
|

16S rRNA gene-based association study identified microbial taxa associated with pork intramuscular fat content in feces and cecum lumen

Abstract: BackgroundIntramuscular fat (IMF) that deposits among muscle fibers or within muscle cells is an important meat quality trait in pigs. Previous studies observed the effects of dietary nutrients and additives on improving the pork IMF. Gut microbiome plays an important role in host metabolism and energy harvest. Whether gut microbiota exerts effect on IMF remains unknown.ResultsIn this study, we investigated the microbial community structure of 500 samples from porcine cecum and feces using high-throughput 16S … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
48
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(52 citation statements)
references
References 55 publications
3
48
1
Order By: Relevance
“…High positive microbial correlation was found between IMF and SFIRM (0.91 ± 0.17), MINA (0.55 ± 0.28) and MINB (0.75 ± 0.27). This agrees with [52] who reported that gut bacteria involved in energy metabolism and intramuscular fat content in pig also regulate the muscle composition and muscle bers. Higher microbial correlation of IMF with minolta color measurements and SFIRM indicated that microbial composition increasing IMF would make the muscle paler and rmer.…”
Section: Correlations Among Meat Quality and Carcass Composition Traisupporting
confidence: 93%
“…High positive microbial correlation was found between IMF and SFIRM (0.91 ± 0.17), MINA (0.55 ± 0.28) and MINB (0.75 ± 0.27). This agrees with [52] who reported that gut bacteria involved in energy metabolism and intramuscular fat content in pig also regulate the muscle composition and muscle bers. Higher microbial correlation of IMF with minolta color measurements and SFIRM indicated that microbial composition increasing IMF would make the muscle paler and rmer.…”
Section: Correlations Among Meat Quality and Carcass Composition Traisupporting
confidence: 93%
“…Concomitant with these changes, the authors reported an increase in circulating inflammatory cytokines (IL-6, TNF-α, and MCP-1) and intramuscular fat after just 3 days [85], suggesting rapid dysregulation of these seemingly inter-connected systems. Regulation of muscle composition by gut microbiota is supported by associations between gut bacteria involved in energy metabolism and porcine intramuscular fat content [86]. Furthermore, age-related changes in gut microbiota have also been proposed to evoke fat infiltration into bone [87, 88], culminating in a triad of aberrant muscle, bone, and adipose tissue dysregulation (osteosarcopenic obesity).…”
Section: Gut Microbiota and Skeletal Muscle Size Composition And Fumentioning
confidence: 99%
“…Gut dysbiosis disrupts the physical and metabolic function in muscles through microbial products such as LPS (29) and gut microbe-derived extracellular vesicles that impair glucose metabolism in skeletal muscle (234). These microbial products leak into the systemic circulation, prompting a proinflammatory response via the release of inflammatory cytokines such as TNF-a and IL-6, culminating in smaller, fat-infiltrated muscles with disrupted insulin signaling pathways and eventually leading to the pathogenesis of metabolic syndrome and sarcopenia (235)(236)(237)(238)(239)(240)(241).…”
Section: Function Of Skeletal Musclementioning
confidence: 99%